Persisting and new onset symptomatology and determinants of functional limitation of post acute COVID-19 syndrome cases- A study from a Northern District of Kerala - Anuradha Thalian Chathoth; Naveen Anaswara; Arjun Chathoth Meethal; Jayasree Vasudevan; Parvathi V Gopal (Wolters Kluwer Medknow Publications, 2023)
Background: COVID-19 disease has a wide range of persisting and new onset clinical manifestations even long after the acute phase. This study was conducted to identify the persisting and new onset symptomatology of post-COVID-19 syndrome patients from clinics in urban and peri-urban Kozhikode, South India, as well as to grade their functional limitation; assess the determinants and predictors. Material and Methods: A cross-sectional study was conducted among 938 subjects attending the post-COVID clinics. Symptom profile, functional assessment, and limitation grading were done using the Post-COVID-19 Functional Status (PCFS) scale. Statistical analyses were done using the SPSS ver.20. Results: Mean age was 41.50 ± 16.90 years. Fever, anosmia, dysgeusia, headache, and myalgia were the common acute COVID-19 symptoms (505,54%; 433,46.3%; 420,44.9%; 323,34.4%; 252,26.9%, respectively). Post-COVID-19, common persisting symptoms were myalgia (167,17.8%), fatigue (149,15.9%), dyspnea (113,12%), and headache (85,9.1%); the common new onset symptoms were shortness of breath and fatigue (228,24.3% and 220,23.4%, respectively). A total of 91 cases (9.7%) had post-COVID sleep disturbances; 16 (1.7%) had symptoms of anxiety and depressive thoughts. PCFS grading showed that 552 (63.8%) had negligible limitations (Grade I). Only one person had Grade IV limitation. Significant association (p < 0.05) was found between functional impairment grading by PCFS and age, gender, locality, type of family, duration of hospitalization, duration of unemployment following illness, source of infection, diabetes mellitus, and hypertension. Male gender, married status, CAD, and smoking had significant higher risks; urban locality and hospitalization decreased the risk. Conclusions: SARS-CoV-2 cases have persistent and new onset symptoms and some degree of functional impairment post-COVID. Significant association was identified for various sociodemographic and clinical variables with the PCFS functional impairment grading.